Innovative optimization approach to improve noise vibration harshness and lightweight in lower control arm. (May 2022) - Messana, Alessandro; Luciano, Ilaria; Ferraris, Alessandro; Airale, Andrea G; Carello, Massimiliana
This paper presents a multi-material design for a lightweight swing arm of a McPherson suspension. Starting from a stamped steel lower control arm (LCA) of a C-segment vehicle a hybrid arm made of a metal core and two Carbon Fiber Reinforced Plastics covers has been hand sketched, Computer Aided Design designed, and Finite Element Method tested. To fully exploit hybridization potential, it has developed a specific methodology which combines the topological optimization of the metal core, and the 3-phase optimization of the composite covers. Also, an innovative viscoelastic material has been included in the laminates to enhance the damping properties of the arm and a Frequency Response Function analysis has been performed. The results in terms of mass, stiffness and stress distribution have been compared with the original stamped steel LCA and with another hybrid LCA design. The final comparison has shown that with the redesign approach it has been possible to reduce the mass to a greater extent without affecting stiffness performance and stress distribution.